Sex education : attitude of adolescents, cultural differences and schools' challenges - Kenny, Maureen C., 1967- (Education in a competitive and globalizing world series., 2014)
This is a contemporary book that addresses global issues in adolescent sexuality education. With chapters from international experts in sexuality, this book provides comprehensive coverage of issues including effective sexuality education, abstinence programs, and risk prevention efforts, drawing on research currently being conducted in schools and agencies across the globe. Emphasizing ""developmentally appropriate sex education"", readers will learn about adolescents' preferences for sources of sex education, as well as the timing and topics that are critical to include. Given an increasing.